Walt Disney's Sleeping Beauty Robyn Bryant ; image adaptation Atelier Philippe Harchy. - Bryant, Robyn; Atelier Philippe Harchy; Walt Disney Company (Montreal, Quebec Brimar Pub., 1993)
Doomed to sleep for one hundred years by a wicked fairy, a beautiful princess finally awakens with the kiss of a prince.
Keywords: Fairy tales; Folklore